Knowledge and Technology Transfer: Trends and Models in Practice of Leading Russian Universities - L. V. Konstantinova; A. M. Petrov; V. V. Vorozhikhin; D. A. Shtykhno (Вестник Российского экономического университета имени Г. В. Плеханова)
The research deals with identification of key trends and models of new practices of the leading Russian universities in the fields of knowledge and technology transfer. Topicality of the research is envisaged by the necessity to adapt the system of higher education in Russia to targets of providing technological sovereignty and leadership, which requires introduction of universities in processes of knowledge and technology transfer, as well as commercialization of innovation. The research used methods of substantial analysis of documents demonstrating the experience of leading Russian universities in the field of knowledge and technology transfer, as well as modeling methods as applied to processes of interaction between universities and industrial partners and assessing university potential in the field of innovation activity. As a result key trends of organizational transformation of universities in the field of knowledge and technology transfer were identified: developing mechanisms of accumulating potential results in intellectual activity; building ecosystem for transfer and commercialization of scientific innovation; extending cooperation with industrial partners in promotion of results of intellectual activity to real sector of economy. Apart from that 4 key models of university and industrial partner interaction were found in the field of knowledge and technology transfer (R&D order, R&D proposals, start-up promotion and joint enterprise setting up); the concept of transfer funnels was presented to describe processes of project selection, researchers and R&D orders; the model of estimating potential of universities in the field of knowledge and technology transfer was worked out, which gives an opportunity to find the current standing of the university and trajectory of development strategy. The article also shows the promising trends in innovation activity of universities with regard to present day’s goals of scientific and technological development of the country.